2017
DOI: 10.1371/journal.pone.0130867
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for urinary incontinence after prostatectomy: A meta-analysis and systematic review

Abstract: BackgroundThis meta-analysis was designed to assess the efficacy of the male sling and artificial urinary sphincter on treating post-prostatectomy incontinence by evaluating daily pad use, cure rate, frequency of improvement in incontinence, and quality of life.MethodsMedline, Cochrane, Google Scholar, and ClinicalTrials.gov were searched (until March 31, 2014) for studies that investigated the effectiveness of artificial urinary sphincter or sling surgical treatments for prostate cancer. The primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
1
19
0
2
Order By: Relevance
“…The results observed in this review were similar to those noted in a systematic review with metanalysis performed by Chen et al, 49 which jointly analyzed all types of sling and found a cure rate of 60% (95%CI: 51%-67%).…”
Section: Discussionsupporting
confidence: 89%
“…The results observed in this review were similar to those noted in a systematic review with metanalysis performed by Chen et al, 49 which jointly analyzed all types of sling and found a cure rate of 60% (95%CI: 51%-67%).…”
Section: Discussionsupporting
confidence: 89%
“…It is important to mention that there are many approaches to treat women with MUI, such as electrical stimulation, 30 surgical, 31 and PFMT, 32 which have shown important improvements. PFM strength has been demonstrating to improve quality of life, 33 decrease urinary leaking, and number of incontinences episodes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Success rates vary between 23% and 73% depending on the definition and duration of follow up. 25,12,14…”
Section: Discussionmentioning
confidence: 99%